A reconsideration of the origin of the early Pleistocene 'Pebble Gravel Formation' at Nettlebed, Oxfordshire, south central England. Issue 4 (August 2016) - Worsley, Peter
Abstract: It is proposed that the meagre 'Nettlebed Gravel' does not merit its designation as the earliest sedimentary archive of the River Thames, nor is it a degraded river terrace. Rather the character of the gravel supports a derivation by slope processes with a quartz/quartzite component primarily sourced by the underlying Palaeogene Reading Formation. The associated Priest's Hill pollen bearing sediments are probably the infill of either a local palaeochannel or a doline. Although the 'Nettlebedian Interglacial' is likely to be early-middle Pleistocene in age, it bears no direct relationship to the Thames fluvial chronology. As a consequence any marine oxygen isotope stage assignment is unrealistic.